Funding and University Performance: An Econometric Analysis of the Indian Public Universities - Kaur , Amanpreet (Gyan Management Journal, 2023)
Underpinning the aim of India’s National Education Policy, 2020 to  devise a performance-based funding mechanism, it is pertinent to  examine the impact of existing financial support on the university’s  performance. Using a fixed panel data analysis, the present study  investigates the influence of funding on the performance of Indian  public universities over the period 2016-2020. The funding is considered  in terms of the plan and non-plan grants received by universities  from the central government, while performance is measured using  performance parameters given by National Institutional Ranking  Framework, 2021. Controlling the age, size and ownership type of  university, findings reveal a significantly positive impact of funding on  teaching performance, research performance and graduation outcomes  of government-owned universities. Surprisingly, university’s outreach,  inclusivity and peer perception have been observed to be indifferent  towards central grants. Overall, the study provides valuable insights to  university practitioners and policymakers for future development of  the performance-funding mechanism.
Keywords: Funding; University performance; Panel data analysis; National Institutional Ranking Framework; National Education Policy